Women and Science : Social Impact and Interaction - Sheffield, Suzanne Le-May, 1967- (Book collections on Project MUSE., 2004)
"This new work examines the challenges and barriers women scientists have faced and chronicles their achievements as they struggled to attain recognition for their work in the male-dominated world of modern science."--Jacket.